Unemployment: Okun's Law, Labor Force, and Productivity - Friedman, Benjamin M.; Wachter, Michael L. (The Review of Economics and Statistics, 1974)
ONE of the most important relationships I in economics is that between the production of real output on the one side and the employment and unemployment of labor on the other. In the familiar breakdown of an economy into its simplest functions a goods market, a labor market, and one or more financing markets1 this relationship comprises the interface between the goods market and the labor market. The relationship is all the more important in that a number of researchers have connected price movements in the goods market directly to quantity movements in the labor market, relying upon both theories of administered pricing and empirical observations of Phillips curve phenomena. Much of current economic thinking relies on the same approach to incorporating the outputunemployment relationship into a macroeconomic framework: Both Keynesians and Chicago school monetarists typically apply their varied apparati to explaining or forecasting movements in real output, and then rely on some type of Okun's Law (1962) formulation to move from real output to a discussion of unemployment. A variant adopted by some neoclassical theorists is to use prices, wages and expectational variables to explain movements in labor market variables -employment or unemployment; these writers then revert, however, to some simplified structure such as the inverse of Okun's Law to move from the labor market to the goods market. For either group, the behavior of whichever market is of primary interest takes precedence over the relationship between the two markets. The object of this paper is to focus clearly on the goods market -labor market nexus. The paper derives and estimates an empirical relationship of Okun's form and shows that this relationship is more complex and merits more explicit attention than the current literature implies. In particular, Okun's approach of estimating the unemployment rate directly constitutes an alternative to estimating employment and labor force separately, and using an identity to solve for the unemployment rate, apart from Okun's paper; this approach has largely predominated in the literature of labor market economics.2 Especially from the standpoint of economic forecasting, at least one revealed weakness of the more commonly used indirect approach has been, in recent experience, its inability to generate accurate predictions of the unemployment rate. Errors made in the various equations of the analysis apparently have not been on the whole sufficiently offsetting to render the indirect approach adequate for forecasting and applied policy work. In this context a single direct unemployment equation may have appeal over a model in which the unemployment forecast is the residual which represents the difference between the labor demand forecast and the labor supply forecast.3 The primary output of the paper is, therefore, an unemployment equation which takes real output as given and introduces other independent variables to improve the specification of the goods market labor market relationship. Hence it is also necessary to